The Wits Institute of religion & art: a centre of dialogue - Shapiro, Joshua (My University, 2018)
The Wits Institute of Religion & Art: a Centre of Dialogue is an architectural research report centering around a proposed Institute which strives to foster "Dialogue"- through a museological and educational exploration of the secular and religious realms - between diverse constituencies and communities and across multiple scales. The report explores ideas of sacred space as conceived by traditional religious thought systems, and the architectural and spatial devices employed in the creation of these holy places. It also looks at the secular realm's sacred space as embodied in the museum, with a focus on the art museum. It charts the evolution of the contemporary museum and it's differing roles in shaping and reflecting ideas of value in society, uncovering hidden machinations and narratives implicit in the museum type. All this is undertaken with a view to applying the lessons and devices of both types to the creation of an Institute and architecture which explores and encourages these ideals of openness and dialogue.
This document is submitted in partial fulfilment for the degree: Master of Architecture (Profesional) at the University of Witwatersrand, Johannesburg, South Africa, 2018
Keywords: Church architecture--South Africa; Sacred space; Spirituality